Contemporary American trauma narratives - Gibbs, Alan, 1968- (Edinburgh : Edinburgh University Press, 2014)
Winner of the 2015 Irish Association for American Studies Peggy O'Brien Book Prize. Examines the representation of trauma in contemporary American fiction and non-fiction. This book looks at the way writers present the effects of trauma in their work. It explores narrative devices, such as 'metafiction', as well as events in contemporary America, including 9/11, the Iraq War, and reactions to the Bush administration. Contemporary American authors who are discussed in depth include Joseph Heller, Kurt Vonnegut, Toni Morrison, Tim O'Brien, Lorrie Moore, Mark Danielewski, Art Spiegelman, Jonathan Safran Foer, Anthony Swofford, Evan Wright, Paul Auster, Philip Roth and Michael Chabon. Contemporary American Trauma Narratives offers a timely and dissenting intervention into debates about American writers' depiction of trauma and its after-effects.
Acknowledgements; Introduction; 1. Twentieth-Century Trauma Narratives: Some Paradigmatic Texts; 2. Traumatic Metafiction and Ontological Crisis; 3. 9/11, Collective Trauma, and Postmodernist Responses; 4. Gulf War Memoirs and Perpetrator Trauma; 5. It Could Happen Here: Trauma and Contemporary American Counterfactuals; Conclusion; Bibliography; Index.
Includes bibliographical references (pages 248-263) and index.
Print version record.
English.
JSTOR
Keywords: American fiction -- 21st century -- History and criticism; Psychology in literature; Psychic trauma in literature; Roman américain -- 21e siècle -- Histoire et critique; Psychologie dans la littérature.; Traumatisme psychique dans la littérature.; Literary theory; LITERARY CRITICISM -- American -- General; LITERARY CRITICISM -- General; American fiction; Psychic trauma in literature; Psychology in literature; 2000-2099; Criticism, interpretation, etc